2015
DOI: 10.1021/acs.joc.5b00904
|View full text |Cite
|
Sign up to set email alerts
|

Halogenative Difluorohomologation of Ketones

Abstract: A method for the difluorohomologation of ketones accompanied by halogenation of a C-H bond is described. The reaction involves silylation, difluorocarbene addition using Me3SiCF2Br activated by a bromide ion, and halogenation of intermediate cyclopropanes with N-bromo- or N-iodosuccinimide. The whole process is performed without isolation of intermediates. The resulting α,α-difluoro-β-halo-substituted ketones can be readily converted into fluorine containing pyrazole derivatives and oxetanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…Either Me 3 SiCF 2 Br or BrF 2 CCO 2 Na may be used as difluorocarbene precursors. In addition, ring opening of the difluorosilacyclopropane intermediate may be induced by an electrophilic source of bromine or iodine yielding 2,2‐difluoro‐3‐haloketones 119 …”
Section: Synthesis Of Difluoroketones By a Fluorinated‐building‐blmentioning
confidence: 99%
“…Either Me 3 SiCF 2 Br or BrF 2 CCO 2 Na may be used as difluorocarbene precursors. In addition, ring opening of the difluorosilacyclopropane intermediate may be induced by an electrophilic source of bromine or iodine yielding 2,2‐difluoro‐3‐haloketones 119 …”
Section: Synthesis Of Difluoroketones By a Fluorinated‐building‐blmentioning
confidence: 99%
“…To improve the procedure, we decided to perform the whole sequence of ketones 1 transformations into the final products without the time‐consuming isolation and purification of enol ethers . For this purpose, the ketones 1 were silylated using a chlorosilane/NaI/NEt 3 combination, and crude silyl enol ethers 2 produced in virtually quantitative yields, were subjected to further reactions with malonyl peroxides 4 without purification (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Silyl Enol Ethers 2 [70] NaI (1.4 mmol, 210.0 mg, 1.4 eq.) was placed in a round bottom flask and dried under vacuum (15-20 mmHg) using a heat gun (gun temperature 100-150°C) for 5 min.…”
Section: Experimental Procedures For Schemementioning
confidence: 99%
“…Several research groups reported the synthesis of mono fluorinated and difluorinated pyrazoles (Figure ) . In 2014, Sandford and co‐workers pioneered the synthesis of difluorinated pyrazoles under microwave irradiation condition, and obtained a mixture of mono‐ and di‐fluorinated compounds in low yield (Figure a).…”
Section: Introductionmentioning
confidence: 99%